Pengaruh Penambahan Kacang Hijau (Vigna Radiata) Terhadap Sifat Organoleptik, Kadar Zat Gizi Dan Daya Terima Kahimela Bars - Hindrian Yulia; Made Darawati; Igde Narda Widiada; Iketut Swirya Jaya (Jurnal Gizi Prima (Prime Nutrition Journal), 2019)
Background: Based on data from Basic Health Research (RISKESDAS) in 2018, the prevalence of chronic energy deficiency (SEZ) in pregnant women nationally is 17.3%. Based on 2017 nutritional status (PSG) monitoring data, the incidence of SEZ pregnant women in West Nusa Tenggara (NTB) is still high at 30.4%. One of the efforts to overcome SEZs in pregnant women is by providing alternative food based on local food (mung bean flour, pumpkin flour and kidney beans) through product development, namely Snack bars which are categorized as snacks as interludes containing high energy and protein. Research Methods: This study was an experimental study in the laboratory with a completely randomized design (CRD) of one treatment, namely the comparison of the addition of mungbean flour by 10%, 20%, 30%, 40%, and 50% from the weight of pumpkin flour and red beans.Research Results: The results showed that the addition of mungbean flour had a significant effect on taste (p = 0.024), the selected product was the formulation of kahimela Bars t3 (30 g mung bean flour) with Energy nutrient content 368.74 kcal, Protein 10.75 grams, 12.06 grams of fat, 54.3 grams of carbohydrates, 19.80 grams of water content and 3.13 grams of ash content, while kahimela bars received power 87% and 13% received.Research Conclusion: Kahimela Bars has the effect of Adding Green Bean Flour to Organoleptic Properties, Nutritional Levels, Power Acceptance and can be used as additional food for the prevention of SEZ pregnant women.